NEW SUBCLASS OF UNIVALENT FUNCTIONS DEFINED BY USING GENERALIZED SALAGEAN OPERATOR - Joshi, S. B.; Sangle, N. D. (Journal of the Indonesian Mathematical Society, 2009)
"Pdf FIle"DOI :Â http://dx.doi.org/10.22342/jims.15.2.46.79-89